Hoaxes on Social Media in the Perspective of Hadith - Nurul Hakim (International Journal of Islamic Studies Issues, 2025)
Purpose- This article aims to analyze hoaxes in the social media ecosystem and formulate a hadith-based digital communication ethical framework that is relevant to the contemporary technological context. Design/Methodology/Approach - This study uses a qualitative method with a literature study approach, by analyzing primary sources in the form of thematic hadiths on communication, honesty, verification, and speaking ethics, as well as secondary sources that discuss hoaxes, social media algorithms, and religious digital literacy. Findings - The results of the study show that the character of hoaxes on social media is influenced by a combination of technological factors (algorithm of engagement), psychological (impulsivity and cognitive bias), and social (symbolic authority and echo chamber). From the perspective of hadith, the principles of ṣidq, amanah, tabayyun, and adab al-qawl have proven to be the foundation in preventing hoaxes and disinformation. However, the application of these principles faces structural obstacles due to the design of digital platforms that prioritize virality over accuracy. Originality/Value - The novelty of this research lies in the effort to integrate hadith about hoaxes not only at the normative-individual level, but also at the structural level through the concept of internalizing the value of hadith into the design of digital platforms. This article offers a conceptual framework of Islamic digital communication ethics that links the principles of hadith, maqaṣid al-shari'ah, and value-sensitive design approaches as theoretical and practical contributions in the study of hoaxes on social media.